Performance of constructed wetland for selenium, nutrient and heavy metals removal from mine effluents. (October 2021) - Etteieb, Selma; Zolfaghari, Mehdi; Magdouli, Sara; Brar, Kamalpreet Kaur; Brar, Satinder Kaur
Abstract: Passive biological treatment using constructed wetlands has been employed as a cost-effective and environmentally friendly alternative for mine effluents treatment in Canada. The current work aimed to assess the performance of a laboratory-scale constructed wetland for the removal of selenium, nutrients and heavy metals. This work achieved a maximum selenium removal rate of 54.13% corresponding to the highest hydraulic residence time (almost 47 days). Typha Latifolia was efficient for selenium assimilation and removal from mine effluent. 4.4% of Se mass was accumulated in the under and aboveground biomass while 32.2% was volatilized . Levels <1.69 mg of selenate, <1.69 mg of selenite, <3.39 mg of selenomethionine and <3.39 mg of unknown selenium species were distributed in the underground biomass while levels <0.75 mg of selenate, <0.75 mg of selenite, <1.51 mg of selenomethionine and <1.51 mg of unknown selenium species were found in T. Latifolia leaves. Ammonia removal was mainly based on a nitrification process confirmed by the decrease of ammonia (>96%) and nitrite in association with the increase of nitrate concentrations in the outlet compared to the inlet. The concentrations of other nitrogen compounds mainly thiocyanate and cyanate have significantly decreased from initial average values of 163 and 22.7 mg.L −1 in the influent to 1.5 and 0.3 mg.L −1 final concentrations, respectively. Orthophosphate concentrations were also efficiently decreased from an influent average value of 21.5 ± 3.3 mg.L −1 to an effluent concentration of 9.1 ± 4.4 mg.L −1 . Understanding the selenium and nutrient removal mechanisms will allow treatment performance enhancement and the development of large-scale constructed wetlands for sophisticated mine effluent treatment. Highlights: Maximum selenium removal rate corresponds to the highest hydraulic residence time. Efficiency of Typha Latifolia for selenium uptake, accumulation and volatilization. Occurrence of selenate, selenite, SeMet and unknown selenium species in plants. Ammonia removal in CW was mainly based on a nitrification process. Decrease of thiocyanate, cyanate and orthophosphate in treated effluent.